Validity and reliability of the A-test in assessing the functional capacity of patients with heart failure - Ilić, Dejan; Tomić, Dragana; Djurdjević, Jovana; Obradović, Slobodan (Vojnosanitetski pregled, 2025)
Background/Aim. Before initiating early rehabilitation, it is essential to assess the functional status of patients with heart failure (HF). Although the Barthel Index (BI) is well-established, the A-test, originally developed for traumatology and orthopedic patients, has recently been introduced into broader clinical practice. The aim of this study was to evaluate the validity and reliability of the A-test in assessing functional status in patients with HF. Methods. The study included patients of both sexes with HF, regardless of age or left ventricular ejection fraction, classified according to the New York Heart Association (NYHA) I–IV class, with Mini-Mental State Examination (MMSE) scores ≥ 24, who were tested daily at the same time. Two experienced senior physiotherapists performed the testing, and they completed the A-test and BI separately. Results. A total of 77 patients were enrolled, two-thirds of whom were male, with a mean age of 72 years and a mean ejection fraction of 41.83% [standard deviation (SD) = 11.46]. The average NYHA class at admission, 2.75 (SD = 1.05), and discharge, 2.42 (SD = 1.12), showed a statistically significant improvement (Z = -4.914, p < 0.001). Content validity was supported by low floor (minimal score = 2.0%) and ceiling (maximal score = 10.8%) effects, a wide range of scores (0–50), and appropriate score distribution. Concurrent validity was confirmed by a strong correlation between the A-test and BI (ρ = 0.991, p < 0.001). Predictive validity was demonstrated, as the A-test score on the first day significantly predicted BI at discharge (β = 0.880, p < 0.001, 95% confidence interval: 1.087–1.562). Construct validity was confirmed through four hypotheses. Patients in NYHA class I–II, with higher MMSE scores and higher left ventricular ejection fractions, scored significantly better on the A-test. Age had a significant effect on the results. The A-test demonstrated excellent internal consistency (α = 0.971) and high inter-rater reliability (κ = 0.842). Conclusion. The A-test is a valid and reliable instrument for evaluating the functional capacity of patients with HF.